The Utilization of the Saudi Visa Bio Application in the Management of Hajj Pilgrim Biometric Data by Ministry of Religious Affairs of Tulungagung Regency - Nurhidayat, Akbar Relida; Yumitro, Gonda; Prasodjo, Haryo (Journal of Development Research, 2025)
Digital transformation has changed the landscape of Jamaah Haji biometric data management significantly, mainly through the collaboration between Saudi Arabia and Indonesia that is embodied in the Saudi Visa Bio application. The study looks at the important role of global media in promoting and introducing Saudi Visa Bio applications to potential Hajj pilgrims worldwide. The research methods used include content analysis of various global media platforms to evaluate the extent to which the international community introduces and accepts such applications. The findings show that the digital transformation in the management of Hajj Pilgrims' biometric data through the Saudi Visa Bio application has improved the efficiency and security of the Haji registration process, as well as provided easier access for Jamaah haji from various States, in the Ministry of Religious Affairs of Tulungagung District of Indonesia. The implications of this research provide a better understanding of how cross-border collaboration and digital technology can improve the management of biometric data in the context of global Hajj registration. Keywords: Saudi Visa Bio Applications, Kemenag district of Tulungagung, Biometric Data Management, Digital Transformation